Evaluasi Tata Kelola Teknologi Informasi Menggunakan Framework COBIT 5 Domain Evaluate, Direct and Monitor (Studi Pada Dinas Komunikasi dan Informatika Provinsi Jawa Timur) - Kasitha Wibriyanti Anindita; Suprapto Suprapto; Yusi Tyroni Mursityo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Dinas Komunikasi dan Informatika Provinsi Jawa Timur (Diskominfo) is a government institution that has the task to prepare materials for implementing government affairs which are under the authority of the Provincial Government of communication and information. In implementing the system on Diskominfo, there are still several deficiencies such as the absence of risk management and lack of human resources in carrying out IT management so that the good information technology governance has not been able to run optimally. From the existence of these constraints, we need an evaluation of information technology governance in Diskominfo East Java using the EDM domain of COBIT 5 framework. The research was conducted to determine the capability level on Diskominfo's information technology governance. The results showed that the capability level subdomain process in, EDM02, EDM04 at level 2 while the capability level value obtained at the EDM03 and EDM05 process is located at level 0 and each sub domain has a Gap value that is 1. In order to the organization reach the expected target level, recommendations are given to monitor IT governance, it is necessary to have written documentation, or named as SOP for risk management and documentation for measurement of information technology performance.